Perlindungan Hukum Bagi Konsumen dalam Perjanjian Pinjaman Online: Legal Protection for Consumers in Online Loan Agreements - Triasih, Dharu; Muryati, Dewi Tuti; Nuswanto, A Heru (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The rapid growth of information technology-based lending and borrowing service providers has apparently not been matched by adequate education to the public, resulting in various effects/risks that arise from the many types of online loans and there are still many companies that are unregistered or illegal as well as the potential for data leaks. the user's privacy that can be misused by the organizing company or other parties. Consumer protection is intended as all efforts that guarantee legal certainty to provide consumer protection, as in Article 1 point 1 UUPK. The existence of this UUPK is to guarantee legal certainty for consumer protection by fulfilling consumer rights. The problem that arises is how is the legal protection for consumers in online loan agreements? What steps have been set by the government in protecting consumers related to fintech / illegal online loans? The normative juridical approach method. Collecting data through interviews, questionnaires, literature study. The data collected includes primary data, secondary data. The research data, both primary and secondary data, will be analyzed qualitatively. The results of this study are legal protection for consumers by carrying out a fintech-based company supervision system that is closely related to consumer protection legal issues which are generally regulated in Law Number 8 of 1999 concerning Consumer Protection. Because one of the keys so that consumers' rights can be protected is from the extent to which regulations related to supervision and supervision systems are carried out by the government (in this case OJK) regarding the fintech companies themselves. The step that must be taken by the government is that its implementation must be guided by the Regulation of the Financial Services Authority No. 77 /POJK.01/2016 concerning Information Technology Lending and Borrowing Services.